Public Service Motivation Dalam Mewujudkan Desa Bebas Stunting : Studi Kasus Desa Mongpok - Rethorika Berthanila; Ahmad Zainuri; Rahmi Mulyasih; Ahmad Sururi; Rachmi Yulianti (Sawala : Jurnal Administrasi Negara, 2023)
Stunting is a health and development issue that necessitates collaboration across sectors and active engagement of the community. Using a qualitative case study approach, this study seeks to investigate the impetus behind public service efforts to accelerate stunting reduction in Mongpok Village, Cikeusal District, Serang Regency. The information was gathered via in-depth interviews. Participating in public services about stunting in Mompok village, including midwives, nutrition workers, family planning instructors, PKK cadres, and the village administration, comprised the research informants. Utilizing PSM (Public Service Motivation) theory, the data were examined. In light of the research findings, the village government demonstrates commendable motivation towards public service through its attentiveness and concern for the issue of stunting, collaboration and accountability among diverse stakeholders, ingenuity, and capability to enhance services